Multi-Stage Fitness Test Performance, V˙O2 Peak and Adiposity: Effect on Risk Factors for Cardio-Metabolic Disease in Adolescents - Dring, Karah J.; Cooper, Simon B.; Morris, John G.; Sunderland, Caroline; Foulds, Gemma A.; Pockley, Alan Graham; Nevill, Mary E. (Frontiers in Physiology, 2019)
The role of physical activity in determining the cardio-metabolic health of adolescents is poorly understood, particularly concerning the effect on low-grade chronic inflammation and the mediating effects of training status, V̇O2 peak and adiposity. Purpose: To examine the effect of training status, V̇O2 peak and adiposity on adolescent cardio-metabolic health. Methods: Following ethical approval, 121 adolescents (11.3 ± 0.8 y) completed the study. Cardio-metabolic health (circulating inflammatory cytokine levels, blood glucose and plasma insulin concentrations) was assessed using a fasted capillary blood sample. Training status was determined by multi-stage fitness test (MSFT) distance and the blood lactate response to submaximal exercise; V̇O2 peak was determined during an uphill graded treadmill test; and adiposity was determined as the sum of four skinfolds. Participants were separated into quartiles based on training status, V̇O2 peak and adiposity. Data were analyzed using two-way between-subjects ANCOVA and multiple linear regression. Results: Participants with the lowest training status (MSFT distance) had higher blood concentrations of IL-6 (3.25 ± 0.25 pg.mL-1) and IL-1β (4.78 ± 0.54 pg.mL-1) and lower concentrations of IL-10 (1.80 ± 0.27 pg.mL-1) when compared with all other quartiles (all p < 0.05). MSFT distance was the only predictor of IL-6 (β = -0.291, p = 0.031), IL-1β (β = -0.405, p = 0.005), IL-10 (β = 0.325, p = 0.021) and fasted blood glucose (β = -0.545, p < 0.001) concentrations. Adiposity was the only predictor of plasma insulin concentration (β = 0.515, p < 0.001) and blood pressure (diastolic: β = 0.259, p = 0.042; mean arterial pressure: β = 0.322, p = 0.011). Conclusion: Enhanced training status, but not V̇O2 peak, was associated with a favorable inflammatory profile in adolescents; whilst adiposity adversely affected metabolic health. These findings demonstrate that enhancing training status and maintaining a healthy body composition has therapeutic potential for preventing the development of cardio-metabolic risk in adolescents.